Carga cognitiva y retención de información mediante 2 técnicas de video en un aula invertida: estudio aleatorizado controlado (2023)
Introduction: Long-term information retrieval, based on the cognitive load derived from the instructional design for the delivery of information, is poorly understood. This study aims to compare the magnitude of three types of cognitive load (intrinsic, extraneous, and germane) and the retention of information generated by two video formats used in the virtual component of an inverted classroom: conventional (PowerPoint slides, Microsoft Corp) and non-conventional (Lightboard). Methods: In this experimental study, 320 medical students were randomly assigned to one of the two formats. Cognitive load was evaluated at the end of the intervention using validated questionnaires. Immediate retention of information and retention at three and six months was assessed through multiple choice questions. Results: The germane load generated by the non-conventional format was significantly higher (p < 0.05). No differences were identified in overall, intrinsic, and extraneous load. Information retrieval was higher in the third month with the conventional format, but not differences were identified at the sixth month of follow-up. Conclusions: The magnitude of the three types of cognitive load and the retention of information is similar when students interact with conventional and non-conventional formats for presenting information.